Regulation of BolA abundance mediates morphogenesis in Fremyella diplosiphon - Singh, Shailendra P.; Montgomery, Beronda L. (Frontiers in Microbiology, 2015)
Filamentous cyanobacterium Fremyella diplosiphon is known to alter its pigmentation and morphology during complementary chromatic acclimation (CCA) to efficiently harvest available radiant energy for photosynthesis. F. diplosiphon cells are rectangular and filaments are longer under green light (GL), whereas smaller, spherical cells and short filaments are prevalent under red light (RL). Light regulation of bolA morphogene expression is correlated with photoregulation of cellular morphology in F. diplosiphon. Here, we investigate a role for quantitative regulation of cellular BolA protein levels in morphology determination. Overexpression of bolA in WT was associated with induction of RL-characteristic spherical morphology even when cultures were grown under GL. Overexpression of bolA in a ∆rcaE background, which lacks cyanobacteriochrome photosensor RcaE and accumulates lower levels of BolA than WT, partially reverted the cellular morphology of the strain to a WT-like state. Overexpression of BolA in WT and ∆rcaE backgrounds was associated with decreased cellular ROS levels and an increase in filament length under both GL and RL. Morphological defects and high reactive oxygen species (ROS) levels commonly observed in ∆rcaE could, thus, be in part due to low accumulation of BolA. Together, these findings support an emerging model for RcaE-dependent photoregulation of BolA in controlling the cellular morphology of F. diplosiphon during CCA.